CRENÇAS DOCENTES SOBRE O ENSINO DE PORTUGUÊS COMO SEGUNDA LÍNGUA PARA SURDOS À LUZ DO SISTEMA DE AVALIATIVIDADE - Góis, Sara de Jesus Cardoso Vogado (2024)
This research is primarily based on teachers' beliefs regarding bilingual education for the deaf, analyzed through the Appraisal System (AS). The main understanding is to investigate the beliefs of teachers who work with deaf students whose first language is sign language and Portuguese is the second. Their perspectives on deaf education in Brazil, experiences, and beliefs about the methodologies used in teaching were considered crucial for evaluation by Systemic Functional Linguistics (SFL), more precisely the Appraisal System (AS). The beliefs were categorized into affect, judgment, and appreciation, and their implications for pedagogical practice were discussed, especially in a bilingual education context. The problem that guided the research was: What are teachers' beliefs about teaching Portuguese as a second language to the deaf? With this research problem, the objectives were to analyze teachers' beliefs about teaching Portuguese as a second language to LIBRAS users in a bilingual education context. To answer the research problem, the specific objectives were based on: Identifying linguistic indices related to teachers' beliefs, contained in the teachers' speeches, based on the criteria proposed by the Appraisal System, attitude subsystem; Categorizing beliefs into affect, judgment, and appreciation, according to the attitude subsystem; Discussing the implications of these beliefs in these teachers' pedagogical practice, in a bilingual education context. From these objectives, with the beliefs analyzed, it was possible to obtain an understanding of the teaching of written Portuguese to deaf students, where teachers share a feeling that leads to an understanding of their methodologies and teaching that brings the student closer to understanding written Portuguese.